Exploration of the flavonoid content of Ziziphus spina-christi leaf extract and antioxidant activity assay through in vitro and in silico methods - Fitrianti Darusman; Taufik Muhammad Fakih; Hilda Aprilia Wisnuwardhani; Teti Sofia Yanti; Dwi Syah Fitra Ramadhan (Universitas Ahmad Dahlan, 2023)
One plant that has the potential as an antioxidant is Ziziphus spina-christi (ZSC) because it contains phenolics and flavonoids. This study aims to determine the flavonoid content both qualitatively and quantitatively and to test the antioxidant activity of ZSC leaf extract using in vitro and in silico attenuation methods. Determination of the total flavonoid content of ZSC leaf extract using a comparison of quercetin. In vitro the antioxidant activity assay of ZSC leaf extract was carried out by measuring the reducing activity of ZSC leaf extract against the radical DPPH using ascorbic acid as comparison, while the in silico method using QSAR and pharmacophore modeling techniques. The results showed that the total flavonoid content obtained from ZSC leaf extract was 0.2515 ± 0.0013 mg QE/g D.W with an IC50 of 58.9296 ppm. This value indicates that ZSC leaf extract has potential as a strong antioxidant. Furthermore, from the in silico method using pharmacophore modeling and QSAR techniques, 8 hit compounds were obtained from the content of ZSC with IC50 QSAR ranging from 6.57 to 0.0004, which was thought to be the metabolite that had the most role in its antioxidant activity. This value indicates that ZSC leaf extract has potential as a very strong antioxidant. It also proves that QSAR and pharmacophore modeling techniques can be used as confirmatory tests for in vitro results in determining the antioxidant activity of natural materials.